PODCAST IMPACTS ON STUDENTS’ LISTENING SKILL: A CASE STUDY BASED ON STUDENTS’ PERCEPTIONS - Sartika Dewi Harahap (Jurnal Inovasi Penelitian, 2020)
Technology has produced prominent contribution on education in this information age. It is well known as Edu technology. The podcast is an alternative teaching media to support students’ Listening Skill. In development of ICT, Podcast is a digital recording which contains a recorded program from television, radio, and interviews by using the internet. The present study was aimed to explore podcast effects on Listening Skill for university students. This study involved fourteen students on second semester of Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal as participants. Questionnaire and interview were the instruments used in this study to collect the data. In conclusion, students moderately engage themselves to sharpen their English namely listening with technology experiences. Most of the participants agreed that they like podcast because it helped them in learning English. Podcast provided tremendous topics and activities which make both teachers and students enrich their knowledge and develop their English skills in educational purposes.